Computing the Cost of Service Projects in Telkaif Town Using Soft Sets and Soft Topology - Askandar, Sabih (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
In this research, we will present a new method of collecting data and performing calculations on it to obtain the required results differently from the usual, at the beginning we will define new concepts of soft sets in soft topological spaces and we will give and explaining many properties of them as soft ii- dense in itself sets, soft ii-connectedness, soft ii-perfection and soft ii-compactness. After that, in the practical part, we will use the concept of soft topology in calculating the cost of service projects in several areas of Telkaif district of Nineveh Governorate in the north of Iraq, whether the cost of projects is in the one area or several areas or all of them using the theory of soft sets in soft topological spaces.